Evaluation of fingerprint pattern among students of Nobel Medical College, Biratnagar, Nepal - Jha, M; Sah, SK; Shah, SK; Roy, S; Shah, DK (Devdaha Medical Journal, 2026)
Introduction: A fingerprint identification system can serve as the most convenient, reliable, and cost-effective method for accurate identification. This system of identification is based on the principle that the skin of the fingertips and the thumb have distinctive ridges whose arrangement and distribution remain unchanged throughout a person’s life, and that no two individuals have identical patterns. So, the objective is to identify the pattern of fingerprints and their correlation with sex among students of Nobel Medical College. Methods: A cross-sectional study was conducted in Nobel Medical College and Teaching Hospital, including 100 medical undergraduate students. Among them, 46 were females, and 54 were males. Fingerprints were taken on a white sheet of paper with the help of a stamp pad. All patterns were confirmed using a magnifying glass. Data analysis was done by using SPSS. Chi-square test of Independence was performed for each finger on the right and left hand. Results: Loops were the predominant pattern across all digits, more frequent in males, particularly on the thumb (58.8%), middle (50.7%), and little (57.9%) fingers, while the whorl pattern was more frequent on the index (66.7%) and ring (58.1%) fingers. In fetmales, the composite pattern was more common on index (66.7%), middle (60.0%), and little (66.7%) fingers, while the arch pattern was more common on thumb (75%) and ting (66.7%) fingers. No significant association was found between the fingerprint pattern and the sex of the individual except in the index finger (p-value 0.001; chi-square test). Conclusion: The findings of this study reveal the most common fingerprint pattern among the selected population, although it does not establish a clear association between the fingerprint pattern and the individual’s sex, except for the index finger. In this case, composite patterns were more common in females, while whorl patterns were prevalent in males. This information could be useful for forensic medicine, anthropology, and genetics.